Biocompatible fluorinated polyglycerols for droplet microfluidics as an alternative to PEG-based copolymer surfactants. Issue 1 (2nd December 2015) - Wagner, Olaf; Thiele, Julian; Weinhart, Marie; Mazutis, Linas; Weitz, David A.; Huck, Wilhelm T. S.; Haag, Rainer
Abstract : Polyglycerol-based triblock surfactants with tailored side-chain composition are exemplified in cell encapsulation and in vitro gene expression studies in droplet-based microfluidics as alternative to PEG-based surfactants. Abstract : In droplet-based microfluidics, non-ionic, high-molecular weight surfactants are required to stabilize droplet interfaces. One of the most common structures that imparts stability as well as biocompatibility to water-in-oil droplets is a triblock copolymer surfactant composed of perfluoropolyether (PFPE) and polyethylene glycol (PEG) blocks. However, the fast growing applications of microdroplets in biology would benefit from a larger choice of specialized surfactants. PEG as a hydrophilic moiety, however, is a very limited tool in surfactant modification as one can only vary the molecular weight and chain-end functionalization. In contrast, linear polyglycerol offers further side-chain functionalization to create custom-tailored, biocompatible droplet interfaces. Herein, we describe the synthesis and characterization of polyglycerol-based triblock surfactants with tailored side-chain composition, and exemplify their application in cell encapsulation and in vitro gene expression studies in droplet-based microfluidics.